Interpretasi Khalayak terhadap Program Acara “Islam Itu Indah” di Trans TV - Mutia Rahmi Pratiwi (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Various religious programs offerings on television now are often displayed with the media benchmarks. One of the propaganda on television shows that attract an audience to this day is the “Islam is Beautiful” (Islam is Beautiful). This programs is packed with easy and humor dominated that the first serious religious event is now beginning to the packaging plesure and fun. This leads to propaganda in the media often override the sanctity of the material essence of religion. Different interpretations arise from two communities of Islam in Indonesia, namely NU and Muhammadiyah. Communal meaning has always been the basis for the informant to interpret media messages related to religion.